Solvent-free synthesis of novel para-menthane-3,8-diol ester derivatives from citronellal using a polymer-supported scandium triflate catalyst - Mafu, Lubabalo; Zeelie, Ben; Watts, Paul (Beilstein Journal of Organic Chemistry, 2016)
The use of natural resources as a chemical feedstock for the synthesis of added-value products is gaining interest; as such we report an environmentally friendly method for the synthesis of para-menthane-3,8-diol from natural citronellal oil in 96% yield, under solvent free aqueous conditions. The acylation of para-menthane-3,8-diol with various acid anhydrides over polymer-supported scandium triflate (PS-Sc(OTf)3) catalyst was subsequently developed, where both hydroxy groups of para-menthane-3,8-diol could be simultaneous acylated under mild reaction conditions to form the corresponding diesters in good yields. The advantages of this method include a simple procedure from natural resources, using solvent-free reaction conditions.
Keywords: acylation; diesters; para-menthane-3,8-diol; PS-Sc(OTf)3